Extension of coastal state jurisdiction in enclosed and semi-enclosed seas : a Mediterranean and Adriatic perspective - Grbec, Mitja (Milton Park, Abingdon, Oxon : Routledge, 2014)
'The current jurisdictional status of the Mediterranean Sea is notably different from other enclosed or semi-enclosed seas. Nearly fifty per cent of the Mediterranean waters are high seas and are therefore beyond the jurisdiction of coastal States, this is despite the fact that there are no points in the Mediterranean Sea where the coasts of two States would be more than 400 nm apart. Such a legal situation generally prevents coastal States from adopting and enforcing their laws on the Mediterranean high seas in respect of many important fields such as the protection and preservation of the marine environment, as well as the conservation of marine living resources. However, when it comes to the Adriatic Sea, a sub-sea and sub-region of the Mediterranean, Croatia has proclaimed an Ecological and Fisheries Protection Zone-EFPZ, Slovenia has proclaimed a Zone of Ecological Protection while Italy has adopted a framework law for the proclamation of its Zone of Ecological Protection without actually proclaiming its regime.This book examines the actual or potential extension of coastal State jurisdiction in the Adriatic Sea against the background of similar extensions elsewhere in the Mediterranean. The work considers what the implications and benefits of the extension of coastal State jurisdiction in the Adriatic Sea would be, as well as the maritime boundary delimitation problems which would need to be resolved. The books assesses the legal nature of Part IX of UNCLOS on enclosed or semi-enclosed seas, which call for enhanced cooperation between States surrounding enclosed and semi-enclosed seas in order to facilitate effective management, conservation, exploration and exploitation of the living resources of the sea. It explores whether Part IX of UNCLOS imposes any duties of cooperation in relation to the extension of coastal State jurisdiction in enclosed or semi-enclosed seas. Drawing all this together the book puts forward practical suggestions as to how the issue of extension of coastal State jurisdiction could be approached in a way which would enhance States existing cooperation and improve the overall governance of the enclosed and semi-enclosed seas both in the Adriatic and beyond. This book will be of interest to interest to academics and students of international law, international and regional organizations dealing with law of the sea matters and government officials.'--
Includes bibliographical references (pages 251-260) and index.
Keywords: Territorial waters -- Mediterranean Region; Maritime law -- Mediterranean Region; Jurisdiction (International law); Law of the sea -- Mediterranean Region